Asuhan Keperawatan Keluarga Pada Keluarga Dengan Infeksi Saluran Pernapasan Akut Di Wilayah Kerja Puskesmas Pauh Kota Padang - Inayah Shabrina; Armaita .; Sandra Dewi; Hasmita . (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Acute Respiratory Tract Infection (ARI) is a common disease in children and is a public health problem because it can disrupt respiratory function and daily activities (WHO 2023). Data from the Pauh Community Health Center in Padang City shows a high incidence of ARI in children, reaching 39.3% in 2025. The purpose of this paper is to describe Family Nursing Care for Families with ARI in the Pauh Community Health Center in Padang City. Acute respiratory tract infections (ARI) are usually transmitted through the upper or lower respiratory tract and can cause various illnesses, from mild to serious. The method used is a case study with a nursing process approach including assessment, diagnosis, intervention, implementation, and evaluation. Case analysis revealed the main problems were ineffective airway clearance, disturbed sleep patterns, and readiness to improve health management. Interventions focused on monitoring respiratory status, providing education on ARI care, improving rest quality, and empowering families in managing their children's health. Results showed improvements in respiratory conditions, sleep quality, and increased family knowledge and involvement in patient care. The recommendation given is that families are expected to be able to carry out independent care, maintain a healthy environment, and utilize health service facilities optimally to prevent complications and recurrence of ARI.